TAFSIR MAQASIDI: PENAFSIRAN AL-QURAN BERBASIS MAQASID AL-SYARIAH - Hasan, Mufti (MAGHZA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2017)
This paper will present a new perspective in understanding the Quran, which is the interpretation of the Quran which is oriented towards achieving the purpose of the shari’a. Contemporary scholars call it the ‘at-tafsi>r al-maqa>s}idi>’ or ‘purposive (maqasidic) exegesis’. This approach is expected to solve the problems faced by exegetes, such as the gap between text and context. The basic assumption of this approach is that the Quran was revealed definite with the aim, so that actually interpret the Quran has exposed that purpose, and reflect on the exegeses context. Theories of maqasid ash-shariah introduced the scholars can serve as the basis of Quran’s interpreting, including Jasser Auda’s theory. Auda assumes sharia work similar to the way the system works. Sharia devices, including the Quran, has six features, namely the nature of the cognition, holistic, openness, interconnection hierarchy, and purposiveness. Based on these features, the author make five steps in the interpretation of the Quran: 1) identifications of verses; 2) identifications of meanings; 3) explorations of maqa>s}id al-syari>’ah, and 4) contextualization of meanings; and 5) conclusion.